PERAN UKURAN PERUSAHAAN (SIZE) DALAM MEMODERASI CORPORATE SOCIAL RESPONSIBILITY DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI - Jendra Jaqualine Jekwam; Sri Hermuningsih (UPAJIWA DEWANTARA: Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2018)
The purpose of this research to find determine the role of firm size (Size) as moderating the influence of Corporate Social Responsibility and Liquidity on the Financial Performance of Mining Companies listed in Indonesia Stock Exchange. The data used in this study are financial statements in 2013 to 2016. The data analysis technique used is multiple linear regression analysis. The sample was selected using purposive sampling technique and obtained 33 companies in each year, so that the number of observations used in this research was 132. The results of this study support the hypothesis that CSR and liquidity have a positive effect on the company's financial performance. From the results of this study also shows the role of firm size (Size) is able to moderate the influence of CSR on the company's financial performance. Company size (Size) is able to moderate the influence of Liquidity on the company's financial performance.Keywords : Corporate Social Responsibility (CSR), Liquidity, Company Financial Performance, Company Size (Size).